PRAKTIK INDUNG BEURANG DI KASEPUHAN CIPTAGELAR DALAM FOTOGRAFI DOKUMENTER - Razan Putra Satriadi; Pitri Ermawati; Syaifudin Iskandar (Specta: Journal of Photography, Arts, and Media, 2021)
This photo creation is entitled "Indung Beurang practice in Kasepuhan Ciptagelar in Documentary Photography" aims to visualize the Indung Beurang Practice in the Kasepuhan Ciptagelar community procession after childbirth. The existence of traditional midwives may disappear if there is no successor, or its existence gone unnoticed. In other words, their existence begins to erode with the presence of modern Midwives.          The method applied in this undergraduate thesis is the theory of journalistic photography in the form of serial photos that are composed into a serial documentary photography so that a story from this practice can be conveyed precisely and clearly. It can also becomes a cultural archive in a visual form. The embodiment processes such as observation, exploration, and experimentation are applied in order to obtain accurate data.          Through the visualization of the Indung Beurang practice, it is hoped that its existence can be known by the community and would be continued to be existed. If the presence of modern Midwives is needed, it would be better if the two of them go together so this practice becomes a cultural archive to be known by the modern world.